Learning Innovations after the COVID-19 Pandemic; Educators Creativity in Conducting Teaching in Indonesia - Nurhidayat, Nurhidayat; Joko Prayitno, Harun; Ratih, Koesoemo; Fahmi Johansyah, Muhammad; Al Fattah, Habib; Puspa Dewi (Jurnal VARIDIKA, 2026)
This study is intended to describe the learning innovations that teachers make during and after the emergency remote teaching in Indonesia. Distance learning that was suddenly implemented due to the Covid-19 pandemic had a broad impact on all aspects of education. It is qualitative research with steps of collecting data through observation and interviews, whether structured or unstructured, documentation, and visual materials. The data were analyzed using grounded theory.  The results showed that there were innovations in methods, development of teaching materials, and teachers-parents communication. Before the pandemic, communication between teachers and parents was mostly done only once a semester, but now teachers communicate with parents more often. Learning methods also vary by integrating various media. Media is no longer just using whiteboards or projectors, but more variations of media are used by teachers. Teaching materials are no longer only from one learning source but are obtained from more varied learning sources.